Features of Russian Strategic Communication before the Peace Summit in Switzerland - Aulin Oleksandr; Aulina Olena (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The article examines the strategic communications carried out by the Kremlinon the eve of the Peace Summit in Switzerland. It was found that Russian strategic communications were differed by the manipulative nature of the interpretation of the events around the Summit and the Russian-Ukrainian warin general. In particular, the Kremlin comprehensively used the communication capabilities of high-ranking officials of the Russian Federation and allied countries, along with the massive involvement of Russian and foreign media to spread Kremlin narratives. The main approaches of Western and Russian experts in determining the essence of the phenomenon of strategic communications are considered. It is shown that, in contrast to Western strategic communications, nature of Russian ones is characterized as openly aggressive. The ultimate goal of such strategic communications is to change cultural valuesin the minds of target audiences. A structural and functional analysis of strategic communications of the Russian Federation, which were used by Moscow during the preparation of the Summit, was conducted. The main methods and narrative constructs used by Russian political technologists have been clarified. It was determined that the narrative base of Russian information attacks consisted of both already known narratives and relatively new ones, in particular "on the need for a preventive nuclear strike". Recommendations are given for increasing the effectiveness of Ukrainian strategic communications in relation to the Russian Federation and its allies, in particular by taking into account the religious and political processes in the Muslim federal districts, as well as in the temporarily occupied Crimea. The research uses a comparative method, methods of sociology, political science, and expert evaluations.